Gastroblastoma in Adulthood—A Rarity among Rare Cancers—A Case Report and Review of the Literature. (28th November 2019) - Centonze, Giovanni; Mangogna, Alessandro; Salviato, Tiziana; Belmonte, Beatrice; Cattaneo, Laura; Monica, Melissa Anna Teresa; Garzone, Giovanna; Brambilla, Cecilia; Pellegrinelli, Alessio; Melotti, Flavia; Testi, Adele; Monti, Valentina; et al.
Abstract : Gastroblastoma (GB) is a rare gastric epithelial-mesenchymal neoplasm, first described by Miettinen et al. So far, all reported cases described the tumor in children or young adults, and similarities with other childhood blastomas have been postulated. We report a case of GB in a 43-year-old patient with long follow up and no recurrence up to 100 months after surgery. So far, this is the second case of GB occurring in the adult age >40-year-old. Hence, GB should be considered in the differential diagnosis of microscopically comparable conditions in adults carrying a worse prognosis and different clinical approach.